Identity, conflict and community art - Guzzanti, Paula; Trinity College Dublin. Irish School of Ecumenics (Trinity College Dublin. Long Room Hub, 2008)
This research, based on an ethnographic study of a community art project from the Atlas Women's Centre in Lisburn, Northern Ireland, examines the contribution of such art programmes to the processes of conflict transformation. Social identity has proven to be a conflictive and tenacious variable that interplays among people in the various contexts of daily life. Although armed conflict in Northern Ireland has ceased, the longstanding disparity among identities continues to hinder understanding and respect between people from Catholic and Protestant backgrounds. This unease is grounded in the historical system of relationships that emerged in the sixteenth and seventeenth century in Ireland. Therefore, if a long-lasting and sustainable peace is to be pursued, government and civil society organisations should engage in the exploration and implementation of strategies which aim to dissolve such disparities.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Community art; Conflict transformation; Northern Ireland -- conflict